2009
DOI: 10.1542/peds.2007-3642
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Sulfate in Severe Perinatal Asphyxia: A Randomized, Placebo-Controlled Trial

Abstract: Postnatal magnesium sulfate treatment improves neurologic outcomes at discharge for term neonates with severe perinatal asphyxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
75
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 24 publications
11
75
2
2
Order By: Relevance
“…Magnesium is a naturally occurring NMDA receptor antagonist which is recommended for clinical use to combat glutamate toxicity and brain damage [4][5][6] . Literature regarding postnatal magnesium therapy after birth asphyxia revealed beneficial effects in some and no beneficial effects in others [7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium is a naturally occurring NMDA receptor antagonist which is recommended for clinical use to combat glutamate toxicity and brain damage [4][5][6] . Literature regarding postnatal magnesium therapy after birth asphyxia revealed beneficial effects in some and no beneficial effects in others [7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…4 Bhat et al found that postnatal magnesium sulfate treatment improves neurologic outcomes at discharge for term neonates with severe perinatal asphyxia. 5 Gathwala et al found that postnatal magnesium sulfate treatment with its neuroprotective action prevents brain injury from bilirubin toxicity. 6 Mohsen et al concluded that phototherapy decrease serum Mg level as it decrease serum bilirubin and there is a positive relation between serum bilirubin and serum Mg levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that there is a positive correlation between plasma ionised Mg levels and severity of hyperbilirubinaemia in newborn. 4,5,6,7,8 Bilirubin exhibits an affinity for the phospholipids of the plasma membrane, such as the N-Methyl-D-Aspartate (NMDA) receptors. Therefore, it seems that the activation of NMDA receptors may induce neuronal injury, which could be blocked by the antagonists of the NMDA receptors.…”
Section: How To Cite This Articlementioning
confidence: 99%
“…Systematic reviews have found a significant reduction in the rate of cerebral palsy in children born to magnesiumtreated women at risk of preterm delivery, 81,82 and a clinical trial found that postnatal magnesium sulfate treatment improves neurologic outcome for term neonates with severe perinatal asphyxia. 83 …”
Section: What Might Be Done?mentioning
confidence: 99%